(untitled) (Communications in Computational Physics, 2020)
We investigate a multirate time step approach applied to decoupled methods in fluid and structure interaction (FSI) computation, where two different time steps are employed for fluid and structure respectively. For illustration, the multirate technique is examined by applying the decoupled β scheme. Numerical experiments show that the proposed approach is stable and retains the same order of accuracy as the original single time step scheme, while with much less computational expense.